Cholangiolytic Changes in Statin-Induced Liver Injury - Preethi Dileep Menon; Tamneet Singh; Hopethe Hubbard; Sarah Hackman; Francis E. Sharkey (Hindawi Limited, 2020)
Atorvastatin is a commonly used oral cholesterol-lowering agent. Side effects associated with statin therapy include arthralgia, myalgia, dyspepsia, weakness, and headache. Prospective and retrospective studies of drug-induced liver injury have identified statin-induced hepatotoxicity, with atorvastatin being the most commonly cited. Associated liver function test elevations have varied from hepatocellular to cholestatic/mixed pattern. We report a case of a 58-year-old woman that illustrates unusual histologic findings associated with a mixed pattern of statin-induced liver injury. While being treated with atorvastatin, the patient exhibited repeated bouts of abdominal pain over a year associated with biliary tree dilation, variably attributed to postcholecystectomy dilation and stenosis of the ampulla of Vater. Following sphincterotomy, the patient's bilirubin normalized but the other liver function tests remained elevated. Liver biopsy revealed portal and lobular inflammation with cholangiolysis. The patient's liver function tests normalized following cessation of atorvastatin therapy.